Estudo de segurança de cosméticos: presente e futuro - Chiari, Bruna Galdorfini; Magnani, Caroline [UNESP]; Salgado, Hérida Regina Nunes [UNESP]; Corrêa, Marcos Antônio [UNESP]; Isaac, Vera Lucia Borges [UNESP] (My University, 2012)
Cosmetics have been used since ancient times and, recently, their consumption has increased greatly in many countries, including brazil, which is the third largest consumer market in the world. Thus, concern for the safety and efficacy of these products should be heightened, even though these products are rarely related to adverse reactions that damage the health. Brazilian law requires manufacturers to subject their products to safety testing, to assess the possible reactions that could be caused by them (irritation, sensitization, systemic effects). To this end, in general, animals have been used as the experimental model, but this practice is being increasingly controlled, so that the scientific community is looking for alternative tests that do not require experimental in vivo models. Thus, this review aims to describe the main biological assays used to assess the safety of cosmetics, as well as in vitro assays that can replace them.

Cosméticos são usados pelo homem desde a antiguidade e, atualmente, o consumo tem aumentado muito, inclusive no Brasil, o terceiro maior mercado no mundo. Assim sendo, a preocupação com a segurança e eficácia destes produtos deve ser intensificada, mesmo sendo produtos raramente relacionados a reações adversas que causem danos à saúde. Para a avaliação das possíveis reações que podem ser apresentadas pelos produtos (irritação, sensibilização, efeitos sistêmicos), a Legislação Brasileira exige que os fabricantes avaliem a segurança e eficácia de seus produtos. Para este fim, em geral, são utilizados animais como modelo experimental o que está sendo cada vez mais evitado, acarretando a pesquisa por métodos alternativos para estas avaliações, que não necessitem de modelos experimentais in vivo. Desta forma, a presente revisão tem por objetivo apresentar os principais ensaios biológicos utilizados para avaliação da segurança de cosméticos, bem como ensaios in vitro que os substituam.
Study of the safety of cosmetics: present and future
Keywords: Safety; Alternative methods; In vitro; Cosmetics; Segurança; Métodos alternativos; In vitro; Cosméticos